Combined and complex treatment of high-differential local-distributed cancer of the thyroid gland - I.V. Deineko (Danylo Halytsky Lviv National Medical University, 2019)
Aim.  To evaluate the results of combined and integrated treatment in patients with locally advanced thyroid cancer.